"Capture" Me if You Can: Estimating abundance of dolphin populations. (2nd April 2016) - Thompson, Jessica; Curran, Mary Carla; Cox, Tara
ABSTRACT: Animal populations are monitored over time to assess the effects of environmental disaster and disease, as well as the efficacy of laws designed to protect them. Determining the abundance of a species within a defined area is one method of monitoring a population. In "Capture" Me if You Can, middle school students will use data collected by biologists at Savannah State University to determine abundance estimates of the common bottlenose dolphin Tursiops truncatus . The activity has two parts that provide a platform for students to explore Ocean Literacy Principles, Next Generation Science Standards, and Common Core Mathematics Standards. In Part 1: Are Populations Protected or in Peril?, students will be introduced to threats to common bottlenose dolphins and will learn about a federal law protecting marine mammals from the impacts of humans by reading a scientific article. Students will improve their scientific literacy by expanding their vocabulary while interpreting the article and constructing responses. In Part 2: Not All Data Are Created Equal, students will learn the process of analyzing qualitative (photographic) data and will come to understand that data are not always numbers. Students will also develop visual–spatial skills and use quantitative data to calculate dolphin abundance.